Estudo da influência do teor de finos dos agregados reciclados mistos nas propriedades das argamassas de revestimento - Oliveira, Rosana Prado (2015)
The expansion of the construction is of great importance for the economic development of the country, due to the prominent position the sector takes in economy, creating jobs, enabling housing, income and infrastructure. However, it is also responsible for serious environmental problems related to the construction processes. Given the current concern about sustainability, recycling of waste from construction and demolition (WCD), it is very important because it reduces environmental impacts such as the extraction of raw natural material and pollution caused by improper disposal of these materials. The recycled waste may be applied in various uses in the construction and the use of recycled sand mortar coating is one of the most viable, since they are not subject to structural efforts. In this study, the research was carried out against the influence of fines content of recycled aggregates in coating mortars. Therefore, mixtures containing 20%, 30%, 40% and 50% of natural aggregate replaced by crushed and sieved recycled aggregate (without fines), had their performance compared to mixtures containing crushed and unsieved recycled aggregate (with fines) and to the reference mixture, which contains as aggregate the natural sand. The WCD, provided by company of Santa Maria, are a mixed of bricks, ceramic blocks, tiles, mortars, concrete waste, rocks and ceramic floors. The materials ratio used was 1: 2: 8 (cement: lime: dry fine aggregate) by volume and the recycled aggregate substitutions for natural aggregate were made by volume. To evaluate the influence of the fines content in mortars with recycled aggregates, were analyzed the main properties of mortars in the fresh state and hardened state and the performance of some of these mortars in a coating system. The study concludes that, mortars with recycled and sieved aggregate showed better properties and lower susceptibility to cracking, relative to mortars with unsieved aggregate. Among they, the mortar with a 30% replacement of natural aggregate by crushed and sieved recycled aggregate, presented the best set of properties.